2007
DOI: 10.1111/j.1460-9592.2006.02171.x
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine as a total intravenous anesthetic in infants

Abstract: In this case report, we describe the use of dexmedetomidine as the sole anesthetic for four infants requiring general anesthesia for direct laryngoscopy and bronchoscopy with spontaneous ventilation. Surgical conditions were adequate and the hemodynamic and respiratory profiles of this technique are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 10 publications
0
43
0
5
Order By: Relevance
“…Dexmedetomidine has been found to be useful in sedation during mechanical ventilation, prevention of emergence delirium, after general anaesthesia and procedural sedation during noninvasive radiological procedures [49]. Munro et al, [50] reported dexmedetomidine as the primary agent for sedation during cardiac catheterization in infants and children.…”
Section: Paediatric Usementioning
confidence: 99%
“…Dexmedetomidine has been found to be useful in sedation during mechanical ventilation, prevention of emergence delirium, after general anaesthesia and procedural sedation during noninvasive radiological procedures [49]. Munro et al, [50] reported dexmedetomidine as the primary agent for sedation during cardiac catheterization in infants and children.…”
Section: Paediatric Usementioning
confidence: 99%
“…The protocol based on fentanyl and midazolam plus isoflurane was adapted to our population of pediatric patients including newborns in especial those with low cardiac index based on the demonstration of its effectivity and safety to promote analgesia and hypnosis while preserving hemodynamic stability in children undergoing cardiac surgery 2,9,10 . The dose of DEX has been more investigated for non-painful procedures such as MRI 4,11,12 , cardiac catheterization 13,14 , or bronchoscopy 15 . Few studies have focused on regimen of doses for children with congenital cardiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…kg -1 .min -1 can reduce the cardiac output 23 . However, DEX has been used in total intravenous anesthesia in doses as high as 10 µg.kg -1 .h -1 without inducing severe hypotension or bradycardia 15,24 . Recently, Mason et al 12 reported that elevated doses of DEX (2-3 µg.kg -1 ) over 10 minutes and infusion of 1.5-3.0 µg.kg -1 .h -1 in children undergoing MRI produce bradycardia in approximately 16% of those patients, but mean arterial pressure and arterial oxygen saturation remain within normal limits.…”
Section: Discussionmentioning
confidence: 99%
“…6 Isolated perfused human placental studies have shown that because of the higher lipophilicity of DXM, there is greater placental tissue retention and minimal transport into the foetal circulation. 7 However, DXM is being safely used in neonates and infants for sedation in intensive care setups. 8 DXM has been safely used as an adjuvant for subarachnoid block in urological, orthopaedic and lower abdominal surgical procedures.…”
Section: Introductionmentioning
confidence: 99%